Sistem Pakar untuk Mengukur Tingkat Akurasi Dalam Mengidentifikasi Kepribadian Menggunaakan Metode Forward Chaining - Johan Danu Wijaya; Yuhandri Yunus (Jurnal Informasi dan Teknologi, 2021)
Personality identification is one of the important things to know yourself and others. This identification is carried out based on the trait symptoms a person has based on the big five personality theory. This study aims to measure the level of accuracy in identifying personality based on visible trait symptoms. The data processed in this study were 10 patients. This data comes from psychology experts at the Faculty of Psychology, Riau Islamic University. The method used to process data is forward chaining. Based on the sample data processing that has been done to identify a person's personality and character, it has an accuracy rate of 100%. The results of this study obtained the type of personality which will then be understood by everyone to be able to identify their personality more deeply.